A high-strength and toughening heat treatment process for thick-walled forgings for pressure vessels

By adopting a high-strength and toughening heat treatment process on large-wall thickness forgings, combined with specific alloy elements and fine heat treatment steps, the problems of brittle fracture, short fatigue life and corrosion of traditional forgings in high-pressure environments are solved, and the high hardness and toughness balance of the material is achieved, and it is suitable for high-demand pressure vessels.

CN118755930BActive Publication Date: 2025-03-18JIANGYIN HENGRUN HEAVY IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410790779.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-03-18
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

Traditional large-wall thick forgings are prone to brittle fracture in high-pressure environments, have short fatigue life, and are easily corroded in specific environments, and have uneven microstructures, so they cannot maintain the toughness of the material while increasing hardness.

Method used

A high-strength and toughening heat treatment process is adopted, including selecting low-alloy steel materials containing a specific proportion of vanadium, molybdenum, manganese, silicon and nickel, and performing gradual preheating, heating, carburizing, rapid cooling and tempering treatment to ensure that the internal grains of the forging are not easily coarsed, forming a high-hard surface and good core toughness.

Benefits of technology

It significantly improves the hardness and toughness of the forgings, enhances the compressive and heavy load resistance, extends the service life, improves corrosion resistance, and forms a stable microstructure suitable for high-demand pressure vessels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118755930B_ABST
    Figure CN118755930B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of material science and metal processing technology, and discloses a high-strength and toughening heat treatment process for thick-walled forgings for pressure vessels, comprising the following steps: S1, selecting a low-alloy steel material containing a specific proportion of vanadium, molybdenum, manganese, silicon and nickel; S2, gradually preheating the forging in a furnace to 450°C to 500°C, and continuously heating for 2 hours; S3, heating the forging to 870°C to 920°C, and adjusting the holding time according to the thickness of the forging to ensure that the heat is fully penetrated; S4, carburizing treatment is performed at 680°C to 720°C for 8 to 12 hours; S5, using oil for rapid cooling, and then air cooling to room temperature. The present invention significantly improves the hardness and toughness of the forging, while enhancing its corrosion resistance and fatigue life, and optimizing the microstructure of the material, so that the forging is suitable for the field of pressure vessel manufacturing with high requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material science and metal processing technology, and in particular to a high-strength and toughness heat treatment process for a thick-walled forging for a pressure vessel. Background Art

[0002] In modern industrial production and engineering applications, pressure vessels are key equipment for storing and transmitting high-pressure fluids, and their safety and reliability are of great concern. Pressure vessels are commonly made of thick-walled forgings, which need to have excellent mechanical properties to withstand high pressure and harsh environments. During the manufacturing process, traditional pressure vessel forgings are usually improved through basic heat treatment processes such as normalizing and tempering to improve their mechanical properties.

[0003] However, these traditional thick wall forgings often face several key problems in practical applications:

[0004] Limited balance of hardness and toughness: Although traditional heat treatment can improve the hardness of the material, it often sacrifices the toughness of the material, making the forgings prone to brittle fracture under high pressure environment.

[0005] Inadequate fatigue life: Conventional forgings have a short fatigue life when subjected to long-term cyclic loading, which limits their use in critical industrial applications.

[0006] Corrosion issues: In certain chemical or marine environments, forgings that are not optimally treated are susceptible to corrosion, increasing maintenance costs and potential safety risks.

[0007] Inhomogeneous microstructure: During traditional heat treatment, the microstructure inside the forging is often not uniform enough, which affects the consistency and predictability of the overall performance.

[0008] In response to the above problems, the industry has tried to adopt a variety of solutions:

[0009] Surface strengthening treatment: such as surface carburizing and nitriding, although it can improve the hardness and wear resistance of the forging surface, the depth is limited and may affect the uniformity of the material inside.

[0010] Heat treatment process: such as adjusting the parameters of normalizing, quenching and tempering to improve the performance of forgings.

[0011] Although these traditional methods have improved the performance of forgings to a certain extent, they usually only involve improvements in a single performance and cannot fully meet the comprehensive requirements of modern industry for high-performance materials. At the same time, these methods cannot maintain the toughness of the material while increasing the hardness. Summary of the invention

[0012] In view of the shortcomings of the prior art, the present invention provides a high-strength and toughness heat treatment process method for thick-walled forgings for pressure vessels, which solves the problem that traditional surface strengthening and heat treatment processes only improve a single performance and cannot fully meet the comprehensive requirements of modern industry for high-performance materials. At the same time, it solves the problem that these methods cannot maintain the toughness of the material while improving the hardness.

[0013] To achieve the above objectives, the present invention is implemented through the following technical solutions: A high-strength and toughening heat treatment process for thick-walled forgings for pressure vessels:

[0014] S1. Select low alloy steel material containing specific proportions of vanadium, molybdenum, manganese, silicon and nickel;

[0015] S2. Preheat the forging gradually in the furnace to 450°C to 500°C and continue heating for 2 hours;

[0016] S3, heat the forging to 870℃~920℃ and adjust the holding time according to the thickness of the forging to ensure that the heat penetrates completely;

[0017] S4, carburizing treatment at 680°C to 720°C for 8 to 12 hours;

[0018] S5, use oil for rapid cooling, then air cool to room temperature;

[0019] S6, performing tempering treatment at 460°C to 550°C for 3 to 4 hours;

[0020] S7. Air cool the forging to room temperature.

[0021] Preferably, the carbon content of the low alloy steel material containing specific proportions of vanadium, molybdenum, manganese, silicon and nickel is 0.30% to 0.45%; wherein, by mass percentage, the vanadium content is 0.10% to 0.25%, the molybdenum content is 0.20% to 0.30%, the manganese content is 1.00% to 1.50%, the silicon content is 0.20% to 0.40%, and the nickel content is 0.30% to 0.80%.

[0022] Preferably, S2 includes:

[0023] S21, gradually heating the forging within the range of 450°C to 500°C;

[0024] S22. During the preheating process, keep the forgings heated evenly for 2 hours to reduce thermal stress.

[0025] Preferably, S3 includes:

[0026] S31, heating the forging to 870°C to 920°C;

[0027] S32. The holding time is adjusted according to the thickness of the forging, and 1 hour is added for every 25mm of thickness to ensure that the temperature fully penetrates.

[0028] Preferably, S4 includes:

[0029] S41, carburizing the forging at a temperature of 680°C to 720°C;

[0030] S42, using gaseous natural gas as a carbon source;

[0031] S43: The carburizing treatment lasts for 8 to 12 hours.

[0032] Preferably, S5 includes:

[0033] S51, using oil as cooling medium;

[0034] S52, rapidly cool the forging from the carburizing temperature to 300°C, with a temperature drop of 15°C to 20°C per minute;

[0035] S53, then switch to air cooling, reduce the temperature from 300°C to room temperature, and reduce the temperature by 10°C to 15°C per hour.

[0036] Preferably, S6 includes:

[0037] S61, heating the forging to 460°C to 550°C for tempering;

[0038] S62, Tempering treatment lasts 3 to 4 hours to eliminate internal stresses and optimize hardness and toughness.

[0039] Preferably, each step in S1 to S7 is performed in an atmosphere-controlled furnace to prevent oxidation and contamination.

[0040] Preferably, the low alloy steel material selected in S1 further includes 0.005% to 0.015% titanium (Ti) to further refine the grains and improve the comprehensive mechanical properties of the forging.

[0041] The invention provides a high-strength and toughness heat treatment process method for thick-wall forgings used in pressure vessels.

[0042] It has the following beneficial effects:

[0043] 1. The present invention adds vanadium, molybdenum, manganese, silicon and nickel elements to low alloy steel, combined with the surface hardening effect after carburizing treatment, improves the hardenability and hardness of the steel, and refines the grains, enhances the toughness and wear resistance of the material, so that the forging can withstand high pressure and heavy load.

[0044] 2. The precisely controlled preheating, heating, carburizing, rapid cooling and tempering treatment processes of the present invention make it difficult for the internal grains of the forgings to coarsen, and make the forgings have a high hardness surface, maintain good core toughness, make the forgings perform better under high impact loads, and extend the service life of the forgings.

[0045] 3. The present invention helps to form a stable microstructure and reduce internal stress by first rapidly cooling and then gradually cooling. At the same time, by controlling the cooling rate, it avoids the internal stress concentration caused by rapid cooling, reduces the risk of cracks and deformation of forgings, ensures the dimensional stability and shape retention of forgings, and makes the forgings suitable for pressure vessels with high precision requirements.

[0046] 4. The present invention avoids the formation of an oxide layer by using an atmosphere-controlled furnace, so that the forging is evenly heated and cooled throughout the entire process, the microstructure is more uniform, and the corrosion resistance of the forging is improved. At the same time, the protective atmosphere prevents impurities from entering the interior of the material, thereby maintaining the high purity of the forging. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0048] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] Please see attached Figure 1 The embodiment of the present invention provides a high-strength and toughness heat treatment process method for thick-walled forgings for pressure vessels, which aims to significantly improve the hardness and toughness of the forgings by combining innovative material selection with sophisticated heat treatment processes, while enhancing their corrosion resistance and fatigue life, and optimizing the microstructure of the material, thereby making the forgings suitable for the high-demand pressure vessel manufacturing field.

[0050] 1. Material selection

[0051] The selected low alloy steel material contains specific proportions of vanadium, molybdenum, manganese, silicon, nickel and titanium. The addition of these elements optimizes the properties of the steel:

[0052] Vanadium and molybdenum: Improve the strength and heat resistance of the material, and are particularly effective in improving the red hardness of steel.

[0053] Manganese and Silicon: Improve strength and toughness, while manganese also helps improve corrosion resistance.

[0054] Nickel: Enhances toughness and corrosion resistance, especially in low temperature environments.

[0055] Titanium: As a powerful grain refiner, it can refine the grains and improve the overall mechanical properties of the forgings.

[0056] 2. Heat treatment process

[0057] The forging is heated to 450℃~500℃ and held for 2 hours. This step helps reduce the thermal stress inside the material and prepares for subsequent high-temperature treatment. Then it is heated to 870℃~920℃ and the holding time is adjusted according to the thickness to ensure that the heat penetrates completely. Then, carburizing treatment is carried out at 680℃~720℃ using gaseous natural gas for 8 to 12 hours to significantly improve the surface hardness and wear resistance. Then, oil is used for rapid cooling and tempering treatment is carried out at 460℃~550℃ for 3 to 4 hours to eliminate internal stress and optimize hardness and toughness. The forging is heated to 870℃~920℃, and finally the forging is cooled to room temperature in air to complete the entire heat treatment process.

[0058] 3. Refinement of environmental control

[0059] During the entire heat treatment process, the atmosphere controlled furnace can effectively create a low-oxygen or oxygen-free environment to prevent oxidation of the forging surface, thereby maintaining its surface quality. It can also reduce the deposition of impurities and avoid unnecessary chemical reactions to further improve the microstructure and quality of the forging surface. It also ensures that the physical and chemical changes during the heat treatment process occur evenly, further improving the mechanical properties and durability of the material.

[0060] In summary, the forgings and the high-strength and toughness heat treatment process method of the present invention provide a high-performance material solution, which significantly improves the comprehensive mechanical properties of thick-wall forgings and is particularly suitable for the high-demand pressure vessel manufacturing field.

[0061] In order to better understand the present invention, the above method is described in detail below in conjunction with specific embodiments.

[0062] Example 1: Basic carbon-vanadium-manganese alloy forging

[0063] Material selection and pretreatment

[0064] Material configuration:

[0065] Carbon content: 0.35%

[0066] Vanadium content: 0.15%

[0067] Molybdenum content: 0.25%

[0068] Manganese content: 1.20%

[0069] Silicon content: 0.30%

[0070] Nickel content: 0.50%

[0071] Titanium content: 0.01%

[0072] Heat treatment process

[0073] Preheating: Heat the forging gradually to 450℃ and keep it for 2 hours.

[0074] Heating: Heat the forging to 870°C for 4 hours.

[0075] Carburizing: Carburizing was performed at 700°C for 10 hours.

[0076] Cooling: Use oil for rapid cooling to 300℃, cooling by 15℃ per minute, and then air cooling to room temperature.

[0077] Tempering: Tempering treatment is carried out at 500℃ for 3 hours.

[0078] Final Cooling: Air cool to room temperature.

[0079] Example 2: High nickel content forgings

[0080] Material configuration:

[0081] Carbon content: 0.35%

[0082] Vanadium content: 0.20%

[0083] Molybdenum content: 0.20%

[0084] Manganese content: 1.30%

[0085] Silicon content: 0.25%

[0086] Nickel content: 0.40%

[0087] Titanium content: 0.012%.

[0088] Heat treatment process

[0089] Preheating: Gradually heat the forging to 460°C and continue heating for 2 hours.

[0090] Heating: Heat the forging to 880°C and keep it for 5 hours.

[0091] Carburizing: Carburizing was carried out at 690°C for 8 hours using natural gas.

[0092] Cooling: Use oil for rapid cooling to 320℃, cooling by 18℃ per minute, and then air cooling to room temperature.

[0093] Tempering: Tempering treatment was carried out at 480°C for 3.5 hours.

[0094] Final Cooling: Air cool to room temperature.

[0095] Example 3: Low-grain-size carbon-vanadium-manganese alloy forgings

[0096] Material configuration:

[0097] Carbon content: 0.40%

[0098] Vanadium content: 0.18%

[0099] Molybdenum content: 0.28%

[0100] Manganese content: 1.40%

[0101] Silicon content: 0.35%

[0102] Nickel content: 0.60%

[0103] Titanium content: 0.009%.

[0104] Heat treatment process

[0105] Preheating: Gradually heat the forging to 470°C and continue heating for 2 hours.

[0106] Heating: Heat the forging to 890°C and keep it for 6 hours.

[0107] Carburizing: Carburizing was carried out at 710°C for 12 hours using natural gas.

[0108] Cooling: Use oil for rapid cooling to 310℃, 20℃ per minute, and then air cool to room temperature.

[0109] Tempering: Tempering treatment was carried out at 520°C for 4 hours.

[0110] Final Cooling: Air cool to room temperature.

[0111] Example 4: High titanium content forgings

[0112] Material configuration:

[0113] Carbon content: 0.45%

[0114] Vanadium content: 0.25%

[0115] Molybdenum content: 0.25%

[0116] Manganese content: 1.50%

[0117] Silicon content: 0.20%

[0118] Nickel content: 0.70%

[0119] Titanium content: 0.014%

[0120] Heat treatment process

[0121] Preheating: Gradually heat the forging to 480°C and continue heating for 2 hours.

[0122] Heating: Heat the forging to 900°C and keep it for 7 hours.

[0123] Carburizing: Carburizing was carried out at 720°C for 10 hours using natural gas.

[0124] Cooling: Use oil for rapid cooling to 290℃, cooling by 17℃ per minute, and then air cooling to room temperature.

[0125] Tempering: Tempering treatment was carried out at 540°C for 3.5 hours.

[0126] Final Cooling: Air cool to room temperature.

[0127] Example 5: Balanced Titanium-Ni Forgings

[0128] Material configuration:

[0129] Carbon content: 0.38%

[0130] Vanadium content: 0.22%

[0131] Molybdenum content: 0.30%

[0132] Manganese content: 1.25%

[0133] Silicon content: 0.30%

[0134] Nickel content: 0.80%

[0135] Titanium content: 0.013%

[0136] Heat treatment process

[0137] Preheating: Gradually heat the forging to 490°C and continue heating for 2 hours.

[0138] Heating: Heat the forging to 920°C and keep it for 8 hours.

[0139] Carburizing: Carburizing was carried out at 700°C for 9 hours using natural gas.

[0140] Cooling: Use oil for rapid cooling to 300℃, cooling by 15℃ per minute, and then air cooling to room temperature.

[0141] Tempering: Tempering treatment was carried out at 460°C for 4 hours.

[0142] Final Cooling: Air cool to room temperature.

[0143] Test experiment 1:

[0144] Experimental purpose: To evaluate the hardness change of the thick wall forgings in the above five embodiments after the high strength and toughness heat treatment process to ensure that they meet the strength requirements of the pressure vessel.

[0145] Experimental materials and equipment:

[0146] Test specimens: forgings prepared according to the above five embodiments.

[0147] Hardness tester: Vickers hardness testing machine.

[0148] Grinding and polishing equipment: used for surface preparation of specimens.

[0149] Experimental steps:

[0150] 1. Sample preparation: Take out samples from each example, and grind and polish each sample to ensure that the surface roughness meets the requirements of the hardness test.

[0151] 2. Hardness measurement: Fix the sample on the Vickers hardness testing machine and use a load of 10kg for hardness test. Measure at least 5 different points on the surface of each sample and take the average value to reduce data error.

[0152] 3. Data recording: record the hardness value of each point and calculate the average hardness.

[0153] The experimental results are shown in Table 1:

[0154] Table 1 Vickers hardness test results of thick wall forgings of Examples 1-5

[0155]

[0156]

[0157] From the data in Table 1, we can get:

[0158] Example 4 exhibits the highest average hardness value (679 HV), indicating that the high titanium content heat treatment process has a significant effect on improving the surface hardness of the forging.

[0159] The average hardness value of Example 5 is the lowest (624 HV), which is due to the combined influence of powder particle size and titanium and nickel contents, which affect the hardness improvement effect.

[0160] The hardness values ​​of other embodiments show the influence of different material compositions and different heat treatment processes on the hardness. Appropriate material configuration and heat treatment process can effectively improve the hardness of forgings.

[0161] Test experiment 2:

[0162] Experimental purpose: To evaluate the impact toughness of the thick-walled forgings in the above five embodiments after high-strengthening and toughening heat treatment process to ensure that they meet the use requirements of pressure vessels.

[0163] Experimental materials and equipment:

[0164] Test specimens: forgings prepared according to the above five embodiments.

[0165] Impact testing machine: Charpy impact testing machine.

[0166] 1. Sample preparation: Place the sample on the Charpy impact testing machine.

[0167] Apply an impact load and record the energy absorbed by the specimen under the impact.

[0168] The samples of each embodiment were tested separately, and the impact absorption energy of each sample was recorded.

[0169] 2. Data Recording:

[0170] Record the impact absorption energy of each sample and calculate the average value to reduce data error.

[0171] The experimental results are shown in Table 2:

[0172] Table 2: Charpy impact toughness test data of thick wall forgings of Examples 1-5

[0173]

[0174]

[0175] From the data in Table 2, we can get:

[0176] Example 4 shows the highest average impact toughness value (75.3 J), indicating that the heat treatment process with high titanium content has a significant effect on improving the toughness of the forging.

[0177] The average impact toughness value of Example 1 is the lowest (59.3 J), but is still within an acceptable range and is suitable for the basic requirements of pressure vessels.

[0178] The impact toughness values ​​of other embodiments are between the above two, which shows the influence of different material configurations and heat treatment processes on the impact toughness of forgings.

[0179] Test experiment 3:

[0180] Experimental purpose: To evaluate the microstructural changes of thick wall forgings in different embodiments after high strength and toughness heat treatment process to ensure that their structural integrity and performance meet the requirements of pressure vessels.

[0181] 1. Experimental materials and equipment:

[0182] Test specimens: forging samples prepared according to the above five embodiments.

[0183] Microscope: optical microscope and scanning electron microscope (SEM).

[0184] Grinding and polishing equipment: used for surface preparation of specimens.

[0185] Etching agent: used for micro-etching of microstructures

[0186] 2. Experimental Procedure

[0187] Sample preparation: Take out the samples from each example and grind and polish each sample using grinding and polishing equipment until a mirror effect is obtained, ensuring that there are no scratches on the surface.

[0188] Microstructure preparation: The polished sample surface is corroded using an etchant suitable for the forging material, such as 4% nitric acid alcohol solution.

[0189] Microstructure observation:

[0190] Use an optical microscope to make a preliminary observation of the surface of the etched samples and record the grain size, morphology and any microscopic defects such as inclusions or twins.

[0191] Data recording and analysis:

[0192] Microstructural images of each specimen were taken and quantitative and qualitative analyses were performed.

[0193] The average grain size, distribution and any significant microstructural features are recorded.

[0194] Experimental setup:

[0195] Corrosive agent: 4% nitric acid alcohol solution.

[0196] Corrosion time: 30 seconds - 2 minutes.

[0197] The experimental results are shown in Table 3:

[0198] Table 3: Metallographic structure analysis results of thick wall forgings of Examples 1-5

[0199]

[0200] From the data in Table 3, we can get:

[0201] Example 4 shows that the finest grain size is 30 μm, which can significantly improve the mechanical properties of the forging.

[0202] The grain sizes of other embodiments are all lower than those of embodiment 4, providing stable and reliable performance and being suitable for conventional applications.

[0203] Through the metallographic structure analysis of the forgings of five different embodiments, this experiment concluded that the differences in the composition and heat treatment process of various materials significantly affect the microstructure and corresponding properties of the materials.

[0204] Test experiment 4:

[0205] Experimental purpose: To evaluate the fatigue life of thick wall forgings in different embodiments after high strength and toughness heat treatment process to ensure that they meet the durability requirements of pressure vessels under repeated loads.

[0206] 1. Experimental Materials and Equipment

[0207] Test specimens: forging samples prepared according to the above five embodiments.

[0208] Fatigue testing machine: Rotary bending fatigue testing machine.

[0209] Data logging equipment: used to record data during loading cycles and specimen rupture.

[0210] 2. Experimental Procedure

[0211] Sample preparation: Take out a round bar sample of standard size from each example, prepare a sample suitable for the rotary bending fatigue tester, and check whether the surface of the sample is smooth and free of defects to ensure the accuracy of the test.

[0212] Fatigue test setup: The specimen is mounted on a fatigue testing machine and the machine is set up to apply a certain amplitude of cyclic bending stress. The stress amplitude should be set according to the service conditions of the forging.

[0213] Conduct fatigue test: Start the testing machine and record the number of cycles of the sample at a given stress amplitude until the sample breaks.

[0214] Data recording and analysis: record the number of cycles (i.e. fatigue life) of each sample, analyze the fatigue performance of forgings of different embodiments, and compare their fatigue life

[0215] Experimental setup

[0216] Load type: Rotational bending load.

[0217] Stress Amplitude: Set based on 50% of the material's yield strength.

[0218] Cycle frequency: According to the equipment standard, usually 50Hz.

[0219] The experimental results are shown in Table 4:

[0220] Table 4: Fatigue life test data of thick wall forgings of Examples 1-5

[0221]

[0222] From the data in Table 4, we can get:

[0223] Example 4 exhibits the longest average fatigue life of 655,000, because the high titanium content therein can significantly improve the material's resistance to fatigue crack growth.

[0224] The average fatigue life of other embodiments is lower than that of embodiment 4, and the overall performance of the material is enhanced through the grain refinement mechanism. This is not only reflected in the higher fatigue life, but also shows the important role of titanium as a grain refiner in improving the fatigue performance of forgings.

[0225] Test experiment 5:

[0226] Experimental purpose: To evaluate the corrosion resistance of the thick-walled forgings in the above five embodiments after high-strength and toughening heat treatment process to ensure their suitability for pressure vessel applications that may face corrosive environments.

[0227] 1. Experimental Materials and Equipment

[0228] Test specimens: forging samples prepared according to the above five embodiments.

[0229] Corrosion testing equipment: electrochemical workstation, including potentiostat and galvanometer.

[0230] Electrochemical cell: A corrosion test cell filled with 3.5% NaCl solution.

[0231] Reference electrode and auxiliary electrode: A standard silver / silver chloride reference electrode and a platinum auxiliary electrode are usually used.

[0232] Sample electrode: The sample serves as the working electrode.

[0233] 2. Experimental steps:

[0234] Sample preparation: The sample in each embodiment is processed into a shape and size suitable for installation in an electrochemical test cell, and the surface of the sample is cleaned to ensure that there is no oil, dust or other impurities.

[0235] Corrosion test setup:

[0236] The prepared sample was fixed in the electrochemical cell as the working electrode.

[0237] Add 3.5% NaCl solution to the electrochemical cell, ensuring that the specimen is completely immersed.

[0238] Connect the reference electrode and the auxiliary electrode.

[0239] Corrosion testing performed:

[0240] Use a potentiometer to set the open circuit potential measurement and record the open circuit potential after stabilization.

[0241] A dynamic potential polarization test was performed, scanning from -250 mV to +250 mV relative to the open circuit potential at a scanning rate of 1 mV / s.

[0242] Record the relationship between potential and current to determine the corrosion current density and corrosion potential.

[0243] Data recording and analysis:

[0244] Calculate and record the corrosion rate of each specimen and calculate the corrosion rate based on the current density.

[0245] The corrosion potential and current density of different embodiments were analyzed to compare their corrosion resistance.

[0246] Experimental setup

[0247] Electrolyte: 3.5% NaCl solution.

[0248] Temperature: Room temperature 25℃.

[0249] Scan rate: 1mV / s.

[0250] The experimental results are shown in Table 5:

[0251] Table 5: Corrosion resistance data of forgings of different embodiments

[0252]

[0253] From the data in Table 5, we can get:

[0254] Example 4 (high titanium content forging) exhibits the best corrosion resistance and has the lowest corrosion current density (60 μA / cm 2 ) and corrosion rate (0.02mm / yr), which shows that high titanium content significantly improves the corrosion resistance of forgings. Since the addition of titanium promotes the formation of a more stable passivation film, it can be concluded that the increase in titanium content significantly affects the corrosion resistance of forgings.

[0255] Example 1 (base carbon-vanadium-manganese alloy forging) exhibits a higher corrosion current density (120 μA / cm 2 ) and corrosion rate (0.05mm / yr), indicating that the low titanium content failed to provide the same level of protection, resulting in it showing poor corrosion resistance.

[0256] Comparative experiment:

[0257] Experimental purpose: To evaluate the comprehensive treatment effect (material configuration heat treatment) and single treatment (material configuration only or heat treatment only) in Example 1, as well as the performance of untreated thick wall forgings, in order to demonstrate the advantages of the synergistic effect of the present invention in improving material properties.

[0258] Experimental groups:

[0259] Experimental group: Example 1 (material configuration + heat treatment)

[0260] Control group 1: Thick-wall forgings with material configuration only.

[0261] Control group 2: Thick wall forgings that were heat treated only.

[0262] Control group 3: thick wall forgings without any treatment.

[0263] Experimental equipment and materials

[0264] Vickers Hardness Testing Machine

[0265] Charpy impact testing machine

[0266] Optical microscopy and scanning electron microscopy (SEM)

[0267] Rotary bending fatigue testing machine.

[0268] Experimental setup and steps

[0269] 1. Hardness test

[0270] Experimental procedures

[0271] Specimen preparation: Select three specimens from each group for hardness testing, ensuring that all specimens are of consistent size and shape and have standardized surface treatment.

[0272] Hardness test: The surface and internal hardness of each specimen were measured using a Vickers hardness testing machine.

[0273] Data recording: Record the hardness value of each sample and calculate the average value.

[0274] 2. Impact toughness test

[0275] Specimen preparation: Make sure the specimen size meets the standards for Charpy impact testing.

[0276] Impact test: The impact absorption energy of each specimen was tested on a Charpy impact tester.

[0277] Data recording: Record the impact energy and calculate the average value of each group.

[0278] 3. Metallographic structure analysis

[0279] Specimen preparation: Samples were taken from each group for metallographic preparation, polishing and etching.

[0280] Microscopic observation: The grain structure was observed using an optical microscope and SEM.

[0281] Data recording: Analyze grain size and distribution, and record microstructural characteristics.

[0282] 4. Fatigue life test

[0283] Specimen preparation: Prepare specimens that meet the specifications of the fatigue testing machine.

[0284] Fatigue test: The test is carried out on a rotary bending fatigue testing machine, and the number of cycles of the sample at a given stress amplitude is recorded until the sample breaks.

[0285] Data recording: Record the fatigue life of each specimen and conduct comparative analysis.

[0286] 5. Corrosion resistance test

[0287] Specimen preparation: Use specimens of the same size for corrosion testing.

[0288] Corrosion test: Electrochemical corrosion test was carried out in 3.5% NaCl solution, and the corrosion current density and corrosion potential were recorded.

[0289] Data logging: Analyze and record corrosion rates and other relevant parameters.

[0290] The comparative experimental data are shown in Table 6:

[0291] Table 6 Comparative test results of different treatment methods for thick wall forgings

[0292]

[0293]

[0294] From the data in Table 6, we can get:

[0295] Hardness analysis:

[0296] The experimental group (material configuration heat treatment) showed the highest average hardness value (640 HV), which reflects that the synergistic effect of material configuration and heat treatment process can significantly enhance the hardness of the material. This is because the material configuration of Example 1 is combined with the heat treatment process to maximize the material performance. During the heat treatment process, carburizing, quenching and tempering steps work together to select alloying elements such as vanadium, molybdenum and nickel to guide the material to harden without embrittlement. This composite effect not only increases the compressive strength of the material, but also improves the wear resistance, thereby significantly improving the hardness.

[0297] The lower hardness of control group 1 (material configuration only) is mainly due to the lack of heat treatment process. Although the same alloy ratio is used, the lack of heat treatment step means that the potential strength of the material is not fully stimulated, resulting in relatively weaker hardness and overall performance of the material.

[0298] Control group 2 (heat treatment only) was heat treated, but because there was no optimized material configuration, the base steel used did not contain enough alloying elements to support the performance improvement after heat treatment. Therefore, despite the heat treatment, its hardness was still not as good as the experimental group.

[0299] The control group 3 (without any treatment) has the lowest hardness because there is neither an optimized configuration of alloy elements nor any heat treatment process applied, so the hardness of the material in its natural state is much lower than that of the treated samples.

[0300] Impact toughness analysis:

[0301] The impact toughness of the experimental group (material configuration and heating treatment) is the highest, which shows that the comprehensive material configuration and heat treatment process not only improves the hardness, but also optimizes the energy absorption capacity and fracture resistance of the material. This is because the heat treatment process (especially tempering) effectively balances the relationship between hardness and toughness, avoiding the problem of hardness and brittleness.

[0302] Control group 1 (material configuration only) did not perform well in the impact test because the internal stress of the material was not released and the lattice defects were not repaired without heat treatment.

[0303] Although the control group 2 (heat treatment only) was heat treated, the effect of the heat treatment was not fully exerted due to the lack of suitable alloy element support, resulting in limited improvement in the toughness of the material.

[0304] The impact toughness of the control group 3 (without any treatment) is the lowest. The untreated material has internal stress concentration and many microscopic defects, which make it easy to break under impact load.

[0305] Metallographic structure analysis:

[0306] The metallographic structure of the experimental group (material configuration heat treatment) showed the finest grain structure, which benefited from the optimized alloying elements and precisely controlled heat treatment parameters, especially the carburizing and rapid cooling processes, which promoted grain refinement and improved the uniformity and comprehensive performance of the material.

[0307] Control group 1 (material configuration only) had coarse grains and uneven microstructure of the material due to the lack of heat treatment, which directly affected its mechanical properties.

[0308] Although the grains of Control Group 2 (heat treatment only) were refined by heat treatment, the effect of grain refinement and its contribution to performance were limited due to the lack of suitable alloying elements.

[0309] The grains of control group 3 (without any treatment) are the coarsest. The grain boundaries of the material without any treatment are obvious and lack of refined structure, which reduces the overall mechanical properties of the material.

[0310] Fatigue life analysis:

[0311] The experimental group (material configuration heating treatment) significantly prolonged the fatigue life through grain refinement achieved by heat treatment. The carburizing and tempering steps in the heat treatment process enhanced the material's cyclic load bearing capacity, enabling it to exhibit higher durability under long-term cyclic stress.

[0312] Control group 1 (material configuration only) had a loose microstructure and short fatigue life due to the lack of heat treatment, indicating that the performance of the material under repeated stress is greatly compromised without heat treatment.

[0313] Although the fatigue life of the control group 2 (heat treatment only) was improved to a certain extent, the effect of the heat treatment was not fully converted into an improvement in fatigue performance because the substrate did not contain the optimized alloy composition.

[0314] The fatigue life of the control group 3 (without any treatment) was the shortest, showing the importance of treatment in improving the performance of the material under fatigue stress.

[0315] Corrosion resistance analysis:

[0316] The experimental group (material configuration heat treatment) showed a lower corrosion current density, indicating that the synergistic effect of heat treatment and alloy element configuration significantly improved the corrosion resistance of the material. In particular, the carburizing and tempering steps not only improved the mechanical properties of the material, but also enhanced the passivation layer on the surface of the material, effectively inhibited the corrosion process, and reduced the corrosion rate of the material.

[0317] Control group 1 (material configuration only) although alloying elements are beneficial to increase the potential corrosion resistance of the material, the lack of heat treatment results in a less compact internal structure and larger grain boundaries, making the material surface more susceptible to corrosion by corrosive media. As a result, the corrosion current density is relatively high, indicating that the material has poor corrosion resistance.

[0318] Control group 2 (heat treatment only) lacked a specific alloying element configuration, so the effect of heat treatment was not fully exerted, resulting in only a limited improvement in the corrosion resistance of the material. This shows that a single heat treatment cannot completely replace the role of alloying elements in improving corrosion resistance.

[0319] The control group 3 (without any treatment) showed a higher corrosion current density, but its short fatigue life also reflected the fragility of the material in extreme environments. The material without any treatment had coarse grain boundaries and many internal defects, which made it easy for the corrosive medium to penetrate and diffuse, resulting in the fastest corrosion rate and the worst corrosion resistance.

[0320] In general, the synergistic effect of material configuration and heat treatment in Example 1 is significantly better than that of single treatment or untreated samples. This synergistic effect not only improves the hardness and corrosion resistance of the material, but also greatly enhances its fatigue resistance and impact toughness, which is crucial for pressure vessels that withstand repeated or sudden loads. Through this optimization treatment, the performance of large-wall forgings has been comprehensively improved, fully demonstrating the effectiveness and practical value of the method of the present invention.

[0321] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-strength and toughening heat treatment process for thick-walled forgings for pressure vessels, characterized in that: S1. Select low alloy steel material containing specific proportions of vanadium, molybdenum, manganese, silicon and nickel; S2. Preheat the forging gradually in the furnace to 450°C to 500°C and continue heating for 2 hours; S3, heating the forging to 870°C to 920°C, and adjusting the holding time according to the thickness of the forging; S4, carburizing treatment at 680°C to 720°C for 8 to 12 hours; S5, use oil for rapid cooling, then air cool to room temperature; S6, performing tempering treatment at 460°C to 550°C for 3 to 4 hours; S7, the forging is air cooled to room temperature; The carbon content of the low alloy steel material containing vanadium, molybdenum, manganese, silicon and nickel in a specific proportion is 0.30% to 0.45%; wherein, by mass percentage, the vanadium content is 0.10% to 0.25%, the molybdenum content is 0.20% to 0.30%, the manganese content is 1.00% to 1.50%, the silicon content is 0.20% to 0.40%, and the nickel content is 0.30% to 0.80%; The S2 includes: S21, gradually heating the forging within the range of 450°C to 500°C; S22. During the preheating process, keep the forgings heated evenly for 2 hours; The S3 includes: S31, heating the forging to 870°C to 920°C; S32, holding time is adjusted according to the thickness of the forging, and 1 hour is added for every 25 mm thickness; The S4 includes: S41, carburizing the forging at a temperature of 680°C to 720°C; S42, using gaseous natural gas as a carbon source; S43: The carburizing treatment lasts for 8 to 12 hours.

2. The high-strength and toughness heat treatment process for thick-walled forgings for pressure vessels according to claim 1 is characterized in that: The S5 includes: S51, using oil as cooling medium; S52, rapidly cool the forging from the carburizing temperature to 300°C, with a temperature drop of 15°C to 20°C per minute; S53, then switch to air cooling, reduce the temperature from 300°C to room temperature, and reduce the temperature by 10°C to 15°C per hour.

3. The high-strength and toughening heat treatment process for thick-walled forgings for pressure vessels according to claim 1 is characterized in that: The S6 includes: S61, heating the forging to 460°C to 550°C for tempering; S62: Tempering treatment lasts for 3 to 4 hours.

4. The high-strength and toughening heat treatment process for thick-walled forgings for pressure vessels according to claim 1 is characterized in that: Each step in S1 to S7 is performed in an atmosphere-controlled furnace.

5. The high-strength and toughness heat treatment process for thick-walled forgings for pressure vessels according to claim 1, characterized in that: The low alloy steel material selected in S1 also includes 0.005% to 0.015% titanium to further refine the grains and improve the comprehensive mechanical properties of the forging.

Citation Information

Patent Citations

  • Machining method for bearing forge piece for motor vehicle

    CN106111874A